The effect of Melampsorella caryophyllacearum (fir broom rust) on the morphological and anatomical traits of Abies nordmanniana subsp. equi‐trojani - Özden Keleş, Seray; Ünal, Sabri; Karadeniz, Mertcan (Wiley, 2021)
AbstractAbies nordmanniana subsp. equi‐trojani (Kazdagi fir), an endemic tree species in Turkey, is increasingly threatened by Melampsorella caryophyllacearum, a fungal pathogen affecting growth and development of trees. In this work, the effect of M. caryophyllacearum on tree growth and wood cell anatomical properties were investigated in four study plots at two different altitudes (low vs. high) and aspects (shaded vs. sunny) in the Ilgaz Mountain area, south‐western Kastamonu, Turkey. Morphology (stem diameter and height), ring widths and anatomical cell characteristics (tracheid and ray sizes) were compared between asymptomatic and symptomatic trees within each plot. Disease incidence tended to increase with decreasing altitude: trees that were grown at relatively low altitude (approx. 1400 m a.s.l.) showed disease incidence, compared with trees at high altitude (approx. 1700 m a.s.l.). At the lower altitude, symptomatic trees had thinner, shorter stems, whereas stem diameter and height did not differ between asymptomatic and symptomatic trees at the higher altitude. In this study, symptomatic trees showed wider growth rings and greater wood cell sizes than asymptomatic trees in each study plot. The study thus suggests that low altitude may lead to higher pathogen damage in trees, and greater disease incidence may be encouraged by northern aspect.
Keywords: 15. Life on land; 3. Good health